The endoscopic surgical resection of intrasellar lesions conserves the hormonal function: A negative correlation to the microsurgical technique - Linsler, Stefan; Senger, Sebastian; Hero-Gross, Renate; Steudel, Wolf Ingo; Oertel, Joachim (Journal of Neurosurgical Sciences, 2021)
BACKGROUND: The endonasal endoscopic approach is still currently under investigation for sellar tumor surgery: A higher resection rate is to be expected and complications should be minimized. The authors report their surgical results of endonasal endoscopic neurosurgery with special focus on postoperative hypopituitarism in comparison to microsurgical procedures. METHODS: Sixty patients received endoscopic endonasal transsphenoidal procedures for sellar pathologies. All patients were followed up prospectively. Asecond group of 60 patients received microsurgical transsphenoidal procedures for sellar pathologies in our neurosurgical department before and were prospectively followed until now. Special attention was paid to hormonal insufficiency and medical substitution. RESULTS: Sixty-eight percent (41 of 60) of the patients who underwent microsurgical procedures showed a new persisting pituitary insuf ficiency postoperatively. Twenty-three patients (55.5%) were substituted with thyroxine, hydrocortisone and sexual hormones and one patient (2.5%) also with ADH cause of global pituitary insufficiency. In 19 cases without any hormonal insufficiency after microsurgical procedures nine patients (47%) showed remnant tumor in follow-up MRI. The patients who underwent endoscopic procedures for pituitary adenomas re vealed significant (P<0.01) less new persistent hormonal insufficiency with 13% of all cases (8/60). Five patients (62.5%) were substituted with thyroxine and hydrocortisone, two patients (25%) substituted with thyroxine, hydrocortisone and sexual hormones and one patient also with ADH because of global pituitary insufficiency. Thereby, in follow-up MRI and hormonal testing, radical tumor resection was detected in 92% in the endoscopic group. CONCLUSIONS: This study seems to indicate that a better intraoperative identification and preservation of pituitary gland is possible in endo scopic transsphenoidal surgery with consecutive lower postoperative hypopituitarism rate.
CRIS-Team Scopus Importer:2023-12-20
Keywords: Endoscopy; Hypopituitarism; Microscopy; Pituitary gland